Reproductive success and survival of hen rock ptarmigan (Lagopus muta) during summer - Aðalsteinn Örn Snæþórsson 1968- (2012)
The rock ptarmigan (Lagopus muta) is a common breeding bird in Iceland and the population shows fairly regular 10-year cycles. Independent of the cycle the population has been declining 4% annually for the last decades and the amplitude is markedly reduced. In this study two questions are addressed. One is whether generalist predators can cause the dampening of the population cycle and the decline of the population. The other is whether there is an age related difference in chick production, which is information needed to refine a population model of the ptarmigan in Iceland. Hens were trapped in two areas in Iceland, one in the north-east in 2009 and 2010 and the other close to the city Reykjavík in the south-west in 2007 and 2008. Two age groups were identified, birds from previous summer (yearlings) and older birds (adults). All hens were radio tagged and monitored once a week during May through August. Mortality causes were estimated as well as reproductive success. The result shows no statistical difference between age groups regarding survival of hens or number of chicks in August while the difference between areas was large. Survival and reproduction were higher in the north-east where the population increased 3.7-fold during the breeding season while in the south-west the population increase was only 1.6-fold. The proximate reason for this difference was high predation by generalist mammalian predators on hens in the south-west and low chick production. Rjúpa (Lagopus muta) er algengur varpfugl á Íslandi og stofninn sýnir reglulegar sveiflur í fjölda. Hver sveifla tekur um 10 ár og margfaldast stofninn milli lágmarks- og hámarksára. Óháð sveiflunum hefur stofninn minnkað um 4% á ári síðustu áratugi og hámörk orðið sífellt lægri. Í þessari rannsókn er leitað svara við tveimur spurningum. Önnur snýr að því hvort aukið afrán á kvenfuglum yfir sumartímann geti verið orsök breytinga í stofnsveiflunum. Hin snýr að því að afla upplýsinga um ungaframleiðslu eftir aldri en þær upplýsingar vantar til að hægt sé ...